Statistical comparison of second generation of Eurocode and Bro 2004 using Set-Based Design - Preliminary design and comparison of design attributes using set-filtration of a concrete frame bridge - Mårtensson, David; Khamporn, Wattana (My University, 2026)
The European commission has announced the complete enforcement of the revised Eurocodes by 2026, raising concerns regarding their influence on design complexity, material requirements, including the environmental impact. This transition toward the updated regulations creates a need to reassess existing design methodologies and evaluate the effects on structural engineering practice. This evolution, at the same time, challenges traditional Point-based design methodology where a single de sign is chosen early, increasing risk of costly redesigns when requirements change in later design phase. To address this limitation, this research applies a computational framework of Set-based design as an alternative design methodology in combina tion with the Finite Element Analysis. Unlike Point-based design, Set-Based de sign maintains a broad, parameterized space of feasible design solutions, improving adaptability in changing requirements while supporting optimization with respect to material use and environmental impact. The research performed a comparative analysis evaluating material efficiency and CO2-equivalent emission regarding shift ing regulatory frameworks.The two regulations compared was the second generation of Eurocodes and the former Swedish bridge design standard corresponding to using the general technical specification Bro 2004 for reinforced concrete frame bridges. The results indicated that from a broad perspective, no discernible difference was seen in material cost and CO2-equivalent emissions between the two standards, both in terms of feasible and not feasible designs. However, the older Bro 2004 framework permitted higher optimization potential when studying the varying feasible designs.
Keywords: Set-Based Design, Eurocodes, Bro 2004, Concrete frame bridge, Prelim inary design, Finite Element Analysis, Environmental impact.